Integrated water resource management plan (IWRMP) in Oman: way forward - Abdulbaqi, Al Khabouri; Muyibi, Suleyman Aremu; Ahmed M. , Thamer; Kabbashi, Nassereldeen Ahmed (IWA Publishing, 2007)
Water resources management is a continuous challenge in the Sultanate of Oman. Owing to its rapid development during the last 30 years, the growing economy has brought an increase in urbanization with a high demand for quality water supplies. Increasing demands to be met include agriculture, population increase and rapid industrial and commercialdevelopment.Thesefactorshavecreatedalotofstressinthewaterresourcesavailabilityinthecountry.This has resulted in degradation of the quality of the water especially in the coastal areas owing to over-pumping and saline intrusion. To satisfy water users’ requirements and safeguard the scarce water resources in the country, an integrated water resources management plan is proposed. This plan is based on the perception of water as an integral part of the ecosystem, a natural resource and a social and economic good, whose quantity and quality determines the nature of its utilization.TheintegratedapproachwillreviewthecurrentwaterresourcessituationintheSultanateofOman(increasing water shortages, deteriorating water quality, stress in water supplies, etc) and incorporate policy options that recognize these elements, develop national water policy and base the demand for and allocation of water resources on equity and efﬁcientuse.TheIntegratedWaterResourcesManagementPlan(IWRMP)willalsoconsiderthecapacitybuildingofthe humanresourcesworkinginthewatersector,thedevelopmentofnewinstitutionsthatwillserveandmatchthisgoal,the integration of water planning into the national economy and, more signiﬁcantly, community participation.